Prevalence and Diversity of Antibiotic Resistant Escherichia coli From Anthropogenic-Impacted Larut River - Chui Wei Bong; Chui Wei Bong; Kyle Young Low; Kyle Young Low; Lay Ching Chai; Lay Ching Chai; Choon Weng Lee; Choon Weng Lee (Frontiers Media S.A., 2022)
Aquatic environments, under frequent anthropogenic pressure, could serve as reservoirs that provide an ideal condition for the acquisition and dissemination of antibiotic resistance genetic determinants. We investigated the prevalence and diversity of antibiotic-resistant Escherichia coli by focusing on their genetic diversity, virulence, and resistance genes in anthropogenic-impacted Larut River. The abundance of E. coli ranged from (estimated count) Est 1 to 4.7 × 105 (colony-forming units per 100 ml) CFU 100 ml−1 to Est 1 to 4.1 × 105 CFU 100 ml−1 with phylogenetic group B1 (46.72%), and A (34.39%) being the most predominant. The prevalence of multiple antibiotic resistance phenotypes of E. coli, with the presence of tet and sul resistance genes, was higher in wastewater effluents than in the river waters. These findings suggested that E. coli could be an important carrier of the resistance genes in freshwater river environments. The phylogenetic composition of E. coli and resistance genes was associated with physicochemical properties and antibiotic residues. These findings indicated that the anthropogenic inputs exerted an effect on the E. coli phylogroup composition, diversification of multiple antibiotic resistance phenotypes, and the distribution of resistance genes in the Larut River.